Political Participation Of People With Defease And Speaking Defects In At The City Of Medan 2019 Election Of The President And Vice President At The City Of Medan - Halking, Halking; Aldatul Amiah Panggabean (International Journal of Educational Research & Social Sciences, 2021)
This study aims to determine the political participation of persons with disabilities in the Pembina State Special School (SLB) in the 2019 general election. The method used in this research is descriptive qualitative. The location in this study is Jl. Guru Sinumba No.10, Helvetia Tim., Kec. Medan Helvetia, Medan City, North Sumatra 20115. Interviews were conducted with students who are speech-impaired and deaf. Data collection techniques used were observation, interviews and documentation. Data analysis techniques used in the study were data reduction, data presentation and data inference. This research is to find out how the political participation of the speech-impaired and deaf at SLB E Negeri Pembina in the presidential and vice-resident elections in 2019 in the city of Medan. The results of the study indicate that the political participation of students who are speech impaired and deaf at SLB E Negeri Pembina in the general election for presidential and vice presidential candidates in 2019 in the city of Medan, it is known that the participation of speech impaired and deaf people in voting is still low. . It can be concluded based on the results of interviews that of the five research subjects I found that two people who were registered in the presidential and vice presidential elections on April 17, 2019 and three other informants were not registered. As for the two registered people, only one person participated in voting.